Adjuvant and neoadjuvant therapy for resectable pancreatic adenocarcinoma - Sohal, Davendra P. S. (Chinese Clinical Oncology; Vol 6, No 3 (June 30, 2017): Chinese Clinical Oncology (Pancreas Adenocarcinoma-I-Guest Editors: Eileen M. O’Reilly, Lei Zheng), 2017)
Resectable pancreatic adenocarcinoma presents the opportunity for cure of this highly lethal disease by allowing complete surgical removal. However, cure rates remain low. Adjuvant therapy following surgical resection is the standard of care. Most data support the use of gemcitabine or 5-fluorouracil in the adjuvant setting, and emerging data indicate gemcitabine plus capecitabine may improve outcomes. Use of adjuvant radiation remains controversial. Ongoing clinical studies will help better define the role of multi-agent regimens as well as radiation in the adjuvant setting. Neoadjuvant therapy holds the promise of allowing early control of systemic disease with increased delivery of aggressive chemotherapy regimens. Prior studies are mostly small, single-institution trials, making it difficult to draw conclusions. Ongoing trials across the world are systematically testing this approach and may lead to a new therapeutic approach to resectable pancreatic cancer.